Methods of solving social problems among secondary school students in Irbid province, Jordan: Theory and practice - Najihah, Abd Wahid; Malak Sami Hasan, Abu Sini; Ahmad Abdullah Ahmad, Abu Sini (2019)
The process of teaching methods of solving social problems is considered one of the most effective steps in teaching and training. This is because it helps the students to find solutions by themselves through research and experiments. It also helps them analyze and organize their ideas in unconventional situations and enables them to make decisions take responsibility for learning. This is what many of the theoretical trends which explained how to solve social problems indicated upon, being that the inability of students to solve social problems leads them to become uncertain, confused and hesitant. Therefore, this study seeks to present a theory on the most important methods of solving social problems among a sample of students in Irbid Province and identify their level of problem-solving. The findings of this study were achieved using a descriptive approach to identify the most important methods of solving social problems and identify the students’ level of solving social problems. The study recommends that there is a need to conduct research on problem-solving methods for other age groups. Hence, this study seeks to teach and train students on the use of theoretical methods that would enable them to overcome their social problems.